Description of Heteracris lecoqi Yetchom-Fondjo & Kekeunou sp. nov. and Heteracris hannai Wandji & Kekeunou sp. nov. and redescription of Heteracris guineensis (Krauss, 1890) (Orthoptera: Acrididae) with comments on its ecology in the Southern part of Cameroon - Wandji, Alain Christel; Yetchom-Fondjo, Jeanne Agrippine; Kekeunou, Sévilor; Kenne, Martin; Missoup, Alain Didier; Tindo, Maurice; Simeu-Noutchom, Alain; Mbadjoun-Nzike, Marcelle; Xu, Sheng-Quan; Djomnang-Nkwala, Alfiery Laurel; Fomena, Abraham (Zootaxa, 2021)
The specimens studied were collected with sweep net and pitfall in the forests, agro-forests, herbaceous fallows, and crop fields of 14 localities in the southern part of Cameroon, from August 2015 to February 2018. The results show that Heteracris hannai sp. nov. and Heteracris lecoqi sp. nov. differ from previously known species of the same genus by the pattern of coloration and the details or shape of the phallic complex. H. lecoqi sp. nov. is characterized by light brownish body; male cercus with flattened, downcurved and obtuse apex; lophus strongly curved; interlophal space with V shape; apodeme of cingulum bow, convergent, with V-shape; valve of cingulum in lateral view longer than apical valve of penis; ramus in ventral view joined. H. hannai sp. nov. is distinct to other species by brown to grey body; male cercus with apex rounded, curved inside; lophus curved; interlophal space with U-shape; apodeme of cingulum thick, slightly parallel, with U shape; valve of cingulum in lateral view hardly longer than apical valve of penis; ramus in ventral view opened. The characteristics of H. guineensis are closer to H. hannai sp. nov. than to H. lecoqi sp. nov. H. lecoqi sp. nov. was collected only in the fallows while H. hannai sp. nov. was collected in the forests, agro-forests, fallows, and crop fields. Compared to H. guineensis, both new species are scarce in the natural vegetation and their distribution area is limited to two and four localities respectively for H. lecoqi sp. nov. and H. hannai sp. nov. All these three grasshopper’s species were recorded as accidental species in all types of vegetation.